Enhancements in the world of digital forensics - Vaddi, Krishna Sanjay; Kamble, Dhwaniket; Vaingankar, Raj; Khatri, Tushar; Bhalerao, Pranil (Institute of Advanced Engineering and Science, 2024)
Currently, the rapid advancement of computer systems and mobile phones has resulted in their utilization in unlawful acts. Ensuring adequate and effective security measures poses a difficult task due to the intricate nature of these devices, thereby exacerbating the challenges associated with investigating crimes involving them. Digital forensics, which involves investigating cyber crimes, plays a crucial role in this realm. Extensive research has been conducted in this field to aid forensic investigations in addressing contemporary obstacles. This paper aims to explore the progress made in the applications of digital forensics and security, encompassing various aspects, and provide insights into the evolution of digital forensics over the past five years.